Pre-operative administration of butorphanol mitigates emergence agitation in patients undergoing functional endoscopic sinus surgery: A randomized controlled clinical trial - Zhang, Xiao; Qi, Siyi; Lin, Zhen; Zhang, Yizhe; Dai, Wanbing; Tian, Weitian; Tian, Jie; Zheng, Li; Su, Diansan; Huai, Xiaorong (Frontiers in Psychiatry, 2023)
Background This study explored the effectiveness of pre-operative intravenous injection of butorphanol in the alleviation of emergence agitation (EA) in patients undergoing functional endoscopic sinus surgery (FESS). Methods Patients (n = 708) were randomized into two groups. The butorphanol group (Group B, n = 358) received butorphanol infusion (20 ug/kg) before anesthesia induction, while the control group (Group C, n = 350) received an equal volume of normal saline infusion. General anesthesia was induced with sufentanil, propofol, and rocuronium, and was maintained with sevoflurane and remifentanil. Vasoactive drugs maintained the hemodynamic indices within 20% of the baseline. Results The incidence of EA was significantly lower in Group B than that in Group C (Group B vs. C: 24.3% vs. 31.4%, respectively; P = 0.034). The times to spontaneous breathing (26.5 min vs. 23.7 min, P = 0.011), verbal response (36.0 min vs. 33.4 min, P = 0.012), and extubation (31.0 min vs. 28.7 min, P = 0.025) were longer in Group B, and the grade of cough (0.33 vs. 0.43, P = 0.024) at extubation in Group B was lower than that in Group C (P = 0.024). The mean arterial pressure at the end of the operation (P = 0.004) and at 5 min after extubation (P = 0.008) was higher and hypotension was less prominent (0.6% vs. 2.6%, P = 0.030) in Group B. Conclusion Pre-operative intravenous injection of butorphanol decreased the incidence of EA after FESS and provided smooth and hemodynamically stable emergence without extending the stay in post-anesthesia care unit. Clinical trial registration https://www.clinicaltrials.gov/, identifier NCT03398759.